Unintended consequences of the earthquake-prone building legislation: An evaluation of two city centre regeneration strategies in New Zealand's provincial areas. (October 2020) - Aigwi, Itohan Esther; Filippova, Olga; Ingham, Jason; Phipps, Robyn
Abstract: This paper describes two city centre regeneration strategies by reviewing existing literature and carrying out case study analysis to examine the approaches to City Centre Regeneration (CCR) pursued by two provincial areas in New Zealand. Findings from the exploratory case study analysis of the two examined cities revealed different approaches to CCR: (i) Invercargill – 'demolition for redevelopment'; and (ii) Whanganui – 'heritage preservation for regeneration'. Whereas the earthquake-prone building legislation has created logical arguments that have put earthquake-prone historical buildings in the spotlight for demolition in areas with weaker attachment to place, the same legislation has been used as a catalyst to provide opportunities for the seismic upgrade and preservation of the earthquake-prone historical buildings in areas with a stronger attachment to place. These discoveries imply that the actions (or inactions) of councils shape the way their communities perceive the value of the historical buildings in their city centres. Also, the decreasing retention and increasing demolitions trends of heritage buildings in New Zealand's provincial city centres as a result of the earthquake-prone building legislation, have now triggered discussions that have contributed to the recent regulatory and financial incentives initiated by the central government to address the unintended consequences of the legislation on the vitality of provincial areas.